Insights From Animal Reproduction 2016
DOI: 10.5772/62121
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Sheep Produced Embryos – Current and Future Perspectives

Abstract: Due to economical and scientific limitations, sheep embryo reproductive technologies are less commercially applied than in other animal species. However, it is very clear that, in the near future, those techniques are expected to have a central role in animal production as a consequence of genetic and reproductive demands. One drawback is that results obtained after sheep embryo cryopreservation are unattractive for commercial purposes. It is expected that a successful cryopreservation of sheep embryos can pus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 199 publications
(362 reference statements)
0
3
0
Order By: Relevance
“…Over the past decades, an increasing demand for ART application in livestock has been observed [8,46,47]. Additionally, delayed childbearing associated to advanced maternal age has now become the main factor leading women to resort to ART [5].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, an increasing demand for ART application in livestock has been observed [8,46,47]. Additionally, delayed childbearing associated to advanced maternal age has now become the main factor leading women to resort to ART [5].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments involving cow [36] and goat [37,38] embryos have shown that the survival of vitrified embryos can be related to several factors, such as the use of different cryoprotectants, exposure time or concentration of vitrification solutions or different stages of embryonic development. Researchers cite several protocols and technical options to improve embryo survival after cryopreservation in goats [39] and sheep [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in cattle, lipolytic agents or chemical delipidators have been successfully applied, increasing the cryotolerance of vitrified embryos (phenazine ethosulfate [212], trans-10 cis-12 conjugated linoleic acid (CLA) [22,208], and forskolin [213]). These chemicals that regulate metabolism were used to reduce embryo lipid content, inducing smaller lipid droplets and fat indexes, thus improving embryonic cryosurvival [22,208,214]. The addition of CLA during culture of sheep IVP embryos also increased their cryotolerance [8].…”
Section: Methods Of Improving the Cryopreservation Of Sheep Embryosmentioning
confidence: 99%